2020
DOI: 10.1002/2211-5463.12987
|View full text |Cite
|
Sign up to set email alerts
|

The high‐risk HPV E6 proteins modify the activity of the eIF4E protein via the MEK/ERK and AKT/PKB pathways

Abstract: Previous studies have proposed that the human papillomavirus (HPV) E6 oncoproteins modify the transcriptional activity of eIF4E through mechanisms dependent on p53 degradation. However, the effect of these oncoproteins on pathways regulating the activity of the eIF4E protein remains poorly understood. Hence, we investigated the mechanisms whereby E6 proteins regulate the activity of the eIF4E protein and its effect on target genes. Overexpression of E6 constructs (HPV-6, HPV-16, HPV-18, and HPV52) showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Cyclins D1 and E1 (encoded by CCND1 and CCNE1 , respectively) are responsible for cell cycle progression. The oncoprotein E6 of HPV can activate the transcription factor eIF4E, and its inhibition in cervical cancer cell lines leads to CCND1 downregulation 50 . Interestingly, cyclin D1 leads to the release of E2F by inducing phosphorylation of pRB, a protein that is already targeted by HPV oncoprotein E7 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclins D1 and E1 (encoded by CCND1 and CCNE1 , respectively) are responsible for cell cycle progression. The oncoprotein E6 of HPV can activate the transcription factor eIF4E, and its inhibition in cervical cancer cell lines leads to CCND1 downregulation 50 . Interestingly, cyclin D1 leads to the release of E2F by inducing phosphorylation of pRB, a protein that is already targeted by HPV oncoprotein E7 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes are related to cell cycle‐related proteins. Studies have demonstrated that HPVE6 upregulates the expression of eIF5A‐1 145 and modulates the activity of eIF4E protein through the MEK/ERK and AKT/PKB pathways 146 . HPV16 E7 increases the expression of pyruvate kinaseM2 (PKM2) and trriggers its nonglycolytic function, fostering cervical cancer cell proliferation 147 .…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…Saha et al reported that AKT upregulates TKT activity by promoting phosphorylation of TKT Thr382, 43 whereas several studies have shown that HPV16 E6 can activate AKT. [44][45][46] Thus, we reasoned that HPV16 E6 oncogene might upregulate TKT enzymatic activity by activating AKT.…”
Section: Hpv16 E6 Upregulates Tkt Activity Via Akt Activationmentioning
confidence: 99%